Mental Health Stigma Reduction Interventions Among Men: A Systematic Review - Jack Sweeney; Shane O’Donnell; Emilie Roche; P. J. White; Paula Carroll; Noel Richardson (American Journal of Men's Health)
Stigma surrounding mental health, particularly among men, remains a significant barrier to men engaging with support services for their mental health. Despite increasing evidence of interventions targeting different aspects of stigma reduction, there is a notable gap in the literature concerning male-specific mental health stigma reduction interventions and on the underlying behavior change techniques (BCTs) used to reduce stigma. The purpose of this review is to synthesize the evidence relating to the impact of mental health stigma reduction interventions among men and to explore the underlying BCTs associated with each intervention. The review was restricted to empirical research reporting on interventions targeting mental health stigma in male-dominated populations. The quality appraisal was conducted using the Mixed Methods Analysis Tool and a narrative synthesis was conducted. Fourteen articles reporting on 11 interventions were included for review, while 20 outcome measures were used. Perceived public stigma attracted the largest number of interventions with a lesser focus on self or personal stigma. Nineteen BCTs were identified across the interventions with information about health consequences and self-monitoring of behavior being the most common followed by credible source, social contact, and behavior practice/rehearsal. This is discussed in relation to the wider literature. The methodological issues highlighted in the articles limit the conclusions and recommendations that can be drawn from the review. Recommendations for further research include standardizing the scales used in stigma measurement, in-depth reporting of intervention descriptions, and greater use of theory to guide intervention development.